1981
DOI: 10.1042/bj1970645
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of human transcortin

Abstract: Human transcortin was purified to apparent homogeneity from plasma by a two-step procedure involving affinity and hydroxyapatite chromatography. The affinity gel incorporated denatured bovine serum albumin as the spacer and cortisol hemisuccinate as the ligand. Although isolated transcortin showed a propensity for spontaneous polymerization according to a geometric progression (1, 3, 9) only one band was observed on sodium dodecyl sulphate/polyacrylamide-gel electrophoresis. Cortisol-binding activity of the is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2004
2004

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…These association constants agree in magnitude with those previously reported for the binding of cortisol, corticosterone, or progesterone to purified human CBG, either in the absence or in the presence of reducing agents (Stroupe et al, 1978;Mickelson et al, 1981Mickelson et al, , 1982 and for the binding of these same steroids to unpurified CBG from human plasma (Westphal, 1971). However, it has been reported that the number of binding sites and the affinity of CBG in human plasma may be underestimated, as compared with those of purified CBG, owing to differences in environment effects (Mueller & Potter, 1981.…”
Section: Resultsmentioning
confidence: 99%
“…These association constants agree in magnitude with those previously reported for the binding of cortisol, corticosterone, or progesterone to purified human CBG, either in the absence or in the presence of reducing agents (Stroupe et al, 1978;Mickelson et al, 1981Mickelson et al, , 1982 and for the binding of these same steroids to unpurified CBG from human plasma (Westphal, 1971). However, it has been reported that the number of binding sites and the affinity of CBG in human plasma may be underestimated, as compared with those of purified CBG, owing to differences in environment effects (Mueller & Potter, 1981.…”
Section: Resultsmentioning
confidence: 99%